Perbandingan Harga Pokok Produksi Menggunakan Metode Full Costing Dan Variable Costing Pada UMKM Batik Mukti Rahayu - Siska Rochayani; Ika Farida Ulfah (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to compare the calculation of Cost of Goods Sold (COGS) using the full costing and variable costing methods. Cost of Goods Sold (COGS) is the total cost incurred during the production process, which includes raw materials, direct labor, and overhead costs to support production activities. The object of the study was Batik Mukti Rahayu, located in Magetan Regency, a business engaged in the batik industry and facing challenges in calculating costs accurately. This study was conducted in July 2025 with a quantitative descriptive approach. Data collection techniques used were interviews and documentation of the production process and business financing. The data obtained were analyzed by calculating Cost of Goods Sold (COGS) using both methods and then comparing the calculation results. The results showed that the full costing method produced a higher Cost of Goods Sold (COGS) value than the variable costing method. This difference was caused by differences in the treatment of fixed costs in each method. The full costing method is considered more relevant for long-term pricing, while the variable costing method is more suitable for short-term decision making. These findings are expected to serve as a reference for business actors in choosing the appropriate cost calculation method, as well as contributing to more effective cost management and pricing strategies. Keywords: Cost of Goods Sold, Full Costing, Variable Costing, Batik Mukti Rahayu, Pricing Strategy